Performance of black pepper varieties as intercrop in coconut gardens in the lower Brahmaputra valley of Assam state, India - Nath, J.C.; Phukon, R.M.; Sumitha, S.; Maheswarappa, H. P.; Patil, Balanagouda (Journal of Plantation Crops, 2021)
Black pepper (Piper nigrum) is well habituated as an inter/under/mixed crop in plantation crops. A field experiment was conducted at Horticultural Research Station (AICRP on Palms), Kahikuchi of Assam Agricultural University for 12 consecutive years (2009-2021) for studying the performance of black pepper varieties/hybrids when grown as intercrop in 38 year old Assam Green Tall. Panniyur-1 produced a higher number of laterals with more spread compared to other varieties. Similarly, a significantly higher number of spikes (134.0), spike length (15.0 cm) and number of berries per spike (82.0) were also recorded in Panniyur-1. Sreekara recorded the lowest spike length (9.8 cm), while IISR Malabar Excel recorded the lowest number of spikes (85.0). Six-year mean dry berry yield indicated that the yield was significantly higher with Panniyur-1 (1.60 kg vine-1) followed by Sreekara (1.49 kg vine-1) and average yield of 1.00 kg vine-1 recorded in IISR Malabar Excel, IISR Thevam and IISR Shakthi. The oleoresin content (11.7%) and piperine content (5.2%) was found highest in Panniyur-1, followed by Sreekara (10.9 % and 4.5%) whereas, the lowest oleoresin content (8.8%) and piperine content (2.9%) were recorded in IISR Malabar Excel and IISR Thevam, respectively. Intercropping of black pepper in coconut garden recorded the highest net return (` 237088 ha-1) and B: C ratio (3.48) followed by Sreekara (` 212764 ha-1; B: C ratio 3.12) and the lowest net return (` 177938 ha-1) and B: C ratio (2.61) were obtained in IISR Malabar Excel.